2019
DOI: 10.1371/journal.pone.0223540
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal death surveillance and response in Ethiopia: Achievements, challenges and prospects

Abstract: BackgroundMaternal and Perinatal Death Surveillance and Response (MPDSR) was a pilot program introduced in Tigray, Ethiopia to monitor maternal and perinatal death. However; its implementation and operation is not evaluated yet. Therefore, this study aimed to assess the implementation and operational status and determinants of MPDSR using a programmatic data and stakeholders involved in the program.MethodsInstitutional based cross-sectional study was applied in public health facilities (75 health posts, 50 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 37 publications
1
54
1
Order By: Relevance
“…In a study from facilities in Northern Ethiopia, only slightly more than half of the facilities were practicing good quality death reviews and took proper action for identified problems. 15 The Ethiopian MDSR, although reported as a success by some 21 is characterized by low coverage (captured 7.4% of expected maternal deaths), low review (reviewed 8% of identified deaths), and low staff participation. 20 Often, factors contributing to bad outcomes (deaths or delays) are stated to be the result of factors outside the control of local health workers and policy makers.…”
Section: Maternal Death Reviews In Ethiopiamentioning
confidence: 99%
See 3 more Smart Citations
“…In a study from facilities in Northern Ethiopia, only slightly more than half of the facilities were practicing good quality death reviews and took proper action for identified problems. 15 The Ethiopian MDSR, although reported as a success by some 21 is characterized by low coverage (captured 7.4% of expected maternal deaths), low review (reviewed 8% of identified deaths), and low staff participation. 20 Often, factors contributing to bad outcomes (deaths or delays) are stated to be the result of factors outside the control of local health workers and policy makers.…”
Section: Maternal Death Reviews In Ethiopiamentioning
confidence: 99%
“…20 Often, factors contributing to bad outcomes (deaths or delays) are stated to be the result of factors outside the control of local health workers and policy makers. 8,15 In a recent qualitative study of MDSR implementation in Ethiopia, Melberg et al showed that highly politicizing maternal deaths, as indicated by the common slogan of "no mother should die while giving birth" everywhere hinders the identification, reporting, review, or assignment of causes to maternal deaths. Health workers and officers leading MDSRs are under so much pressure to meet the political requirement of zero maternal deaths that there is a strong incentive to substantially underreport.…”
Section: Maternal Death Reviews In Ethiopiamentioning
confidence: 99%
See 2 more Smart Citations
“…MDSR makes each maternal death a notifiable event, and con rms that communities and facilities report and respond to end preventable maternal deaths (19). Despite the importance of MDSR in producing up to date information for decision making, evidence on the process and implementation is lacking (20).…”
Section: Introductionmentioning
confidence: 99%